Entrepreneurial Orientation and Resilience in SMEs: Exploring the Mediating Roles of Reconfiguration and Absorptive Capacity - Asare-Kyire, Lydia; Ackah, Owusu; Bonsu, Charles Akomea; Appienti, William Ansah (An Overview on Business, Management and Economics Research Vol. 7, 2024)
This chapter explores the interconnected roles of entrepreneurial orientation (EO), organizational reconfiguration, absorptive capability, and organizational resilience, particularly in the context of Small and Medium Enterprises (SMEs). This multifaceted approach addresses a notable gap in existing literature, where these relationships have not been simultaneously examined, especially in the SME sector. Two important research topics in management and organizational studies are entrepreneurship and organizational resilience. Although there may be connections among EO, organizational reconfiguration, absorptive capacity, and resilience, few studies—particularly those focusing on Small and Medium Enterprises (SMEs)—have looked at these connections concurrently. By investigating the mediating roles of organizational reconfiguration and absorptive aptitude in the relationship between EO and organizational resilience, this study fills this knowledge vacuum. The study findings revealed that entrepreneurial orientation dimensions have a significant and positive impact on organizational resilience. Highlighting EO's positive impact on resilience, the research emphasizes the critical role of an entrepreneurial mindset in adapting to market changes and seizing opportunities. It specifically underlines the mediating role of absorptive capabilities, indicating their importance in enhancing SMEs' resilience. While organizational reconfiguration showed no direct impact, the findings offer practical guidance for SMEs to focus on entrepreneurial behavior and invest in absorptive capacities, thereby contributing to economic growth and informing policies that support a more resilient SME landscape in Ghana. The results suggest that SMEs that are more entrepreneurial are better equipped to adapt to changes in the market, take calculated risks, be proactive, and seek new opportunities. The study provides considerable contributions to academic research in the fields of entrepreneurship and organizational resilience, especially in the context of SMEs. Its findings are academically relevant and offer practical insights for business leaders and policymakers, making it a valuable addition to the current body of knowledge.